2014
DOI: 10.1016/j.sbspro.2014.11.130
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing the Choice of Solutions for Human Resource Development

Abstract: The paper describes an approach to formalize the choice of solutions for human resource development during the planning process. Although it is traditionally considers a manual process in which the so-called "biased human factors" influence decisions, the research acknowledge and define 12 factors that influence the choice. The author proposes ways to formalise these factors and that would allow creating a human resources development-planning model with automated planning decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…The Hartwick College has also developed some questionnaires in order to evaluate the performance of coaches by the Head coaches, the department of physical education, the samelevel coaches, students and sports captains (27). The findings of the present study regarding the importance of performance evaluation of human resources in the development of human resources are consistent with the findings of some other studies (7,20,21,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The Hartwick College has also developed some questionnaires in order to evaluate the performance of coaches by the Head coaches, the department of physical education, the samelevel coaches, students and sports captains (27). The findings of the present study regarding the importance of performance evaluation of human resources in the development of human resources are consistent with the findings of some other studies (7,20,21,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 88%
“…He reported that as a result, the human resource development could improve the performance of an organization (7).…”
Section: Introductionmentioning
confidence: 99%
“…Dari perencanaan itu dikumpul kemudian kita buat dokumen perencanaan, dan kita masukkan ke Bappeda kabupaten. Dari Bappeda nantinya akan ada pembahasan di Pemerintah pada sektor kesehatan memiliki peran dalam pengawasan untuk memastikan kepatuhan organisasi terhadap rencana strategis jangka menengah, memberikan deskripsi pekerjaan, menilai kinerja, memilih staf untuk mengikuti kegiatan pelatihan, memantau secara rutin dan melaporkan indikator kualitas dalam pemberian pelayanan kesehatan dan penanganan kekerasan di tempat kerja dan keselamatan pasien [6].…”
Section: A Peran Aktor Pelaksana Kebijakanunclassified
“…Computerising HR process 12 reduces the time it takes to complete the task without compromising the quality of work. The e-HRD software 14 relieves the HR department from tedious repetitive manual tasks. By computersing standard and repetitive HR activities, Combat Vehicles Research & Development Establishment (CVRDE) has reduced the cost and time spent on manual HR processing in a lean manpower authorised environment.…”
Section: Introductionmentioning
confidence: 99%